The Effect of Resistance Band And ABC Drill Exercises on The Frequency And Speed of Scrick Kicks of Pencak Silat Athletes Puslatcab Pagar Nusa Surabaya City - Amirulloh Karim; Afif Rusdiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research was based on my visit to Puslatcab Pagar Nusa, Surabaya City, at that time the athletes were practising sparring and I saw a lack of speed in their crescent kicks. The purpose of this study was to determine the effect of Resistance Band and ABC Drill training on the Frequency and Speed of crescent kicks of Puslatcab Surabaya City athletes. This study used an experimental method with a "pretest-posttest design" design. The sample in this study was 20 male pencak silat athletes from Puslatcab Surabaya City. The sampling technique used purposive sampling and was divided using an ordinal pairing frequency test, with several criteria as follows: a) male gender, b) Age 14-17 years, c) pencak silat athletes from Puslatcab Surabaya City. Data analysis used the Wilcoxon signed rank test. The study showed that: 1) there is an effect of Resistance Band and ABC Drill training on the Frequency and Speed of Crescent Kicks of Puslatcab Surabaya City Athletes, with a significance value (Asymp. Sig. 2-tailed) of 0.000 for both data pairs, namely the frequency and speed of the crescent kick. This significance value is smaller than 0.05 (0.000 <0.05) there is an increase. From the change in the average pretest results of the pretest frequency variable research which got an average of 16.2, for the post-test results the frequency variable got an average of 17.2 so that there was a difference of 1 point, then it was stated that there was an increase of 6.17%. And while for the speed variable, the pretest got an average of 5.903, for the post-test results the speed variable got an average of 6.142, so there was a difference of 0.239 points, then it was stated that there was an increase of 4.03%. Suggestion: You can apply Resistance and ABC Drill exercises considering that these exercises not only have the potential to increase Frequency and Speed but are also relatively easier to do and develop further.